Effect of intrauterine perfusion of human chorionic gonadotropin before embryo transfer after two or more implantation failures: A systematic review and meta-analysis. (December 2019) - Xie, Hebin; Zeng, Hong; He, Dongmei; Liu, Nenghui
Abstract: Objective: To investigate whether intrauterine perfusion of hCG before embryo transfer (ET) is effective in women experienced two or more implantation failures. Study design: Systematic review and meta-analysis. In the current meta-analysis, Pubmed, EMBASE and The Cochrane Library were searched for trials which compared the efficacy of intrauterine perfusion of hCG with no perfusion of hCG in women undergoing in vitro fertilization (IVF), intracytoplasmic sperm injection (ICSI), or frozen embryo transfer (FET) before ET. The primary outcomes are the clinical pregnancy rate (CPR) and live birth rate (LBR). Results: Six trials consisted of 1432 women were eligible for quantitative analysis. CPR (including 6 trials consisted of 1432 women) and LBR (including 3 trials consisted of 870 women) were significantly improved in the hCG group compared to the control group, with a CPR of 41.8 % vs. 31.2 % (RR 1.30, 95 % CI 1.14∼1.50, P  < .001), an LBR of 27.8 % vs. 18.0 % (RR 1.52, 95 % CI 1.18∼1.96, P  = .001). Conclusion: Intrauterine perfusion of hCG is effective in improving clinical pregnancy rate and live birth rate in women who experienced two or more implantation failures, which might provide a potential therapeutical intervention for recurrent implantation failure (RIF). Although promising, further evidence from multicenter, randomized controlled trials are needed to confirm the conclusion from the current meta-analysis.